The Apathy Syndrome: How We Are Trained Not to Care about Politics. (3rd July 2019) - Zhelnina, Anna
Abstract: The role of emotions in social movements and mobilization has been an important focus of recent research, but the emotional mechanisms producing apathy and non-participation remain under studied. This article explores the thinking and feeling processes involved in the production of apolitical attitudes, paying particular attention to their social and cultural context. Cultural norms of appropriateness and emotional expression can hinder or boost the emotions involved in the mobilizing processes. Based on 60 interviews with young people in two Russian cities, collected during and in the aftermath of the anti-regime protests of 2011–12, I explore the apathy syndrome—a combination of emotional mechanisms and cultural norms that produce political apathy. Personal frustrating experiences develop into long-term cynicism and disbelief in the efficacy of collective action, a process exacerbated by the transmission of apathy in families and educational institutions, as well as by cultural norms of appropriate emotions. Cultural clichés and dissociation from others help people cope with the trap and justify inaction.